2021
DOI: 10.1021/acs.analchem.1c01484
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Simultaneous Detection of Multielements in Aqueous Samples Based on Biomimetic Array Combined with Laser-Induced Breakdown Spectroscopy

Abstract: Ultrasensitive detection of metallic elements in liquids has attracted considerable attention in fields such as environmental pollution monitoring and drinking water quality control. Hence, it is of great significance to develop a sensitive and simultaneous detection strategy for multiple metal elements in liquid. Laser-induced breakdown spectroscopy (LIBS) technology shows unique advantages because of its simple, rapid, and real-time in situ detection, but the laser energy will be greatly attenuated in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…18,19 Literature shows that the double pulse technique increases the liquid LIBS signal and thereby its sensitivity by using an extra laser pulse to preheat the plasma-induced by the laser in a liquid environment. [20][21][22][23][24][25] In addition, resonance LIBS by choosing a suitable laser wavelength to employ, circulating the sample through a liquid jet, [26][27][28][29] creation of aerosols 30,31 and liquid droplets, 32,33 liquid to solid transformation using different substrates, [34][35][36][37][38][39][40][41] etc., are the other proposed methods for liquid LIBS analysis till date. Among them, adding the components to the experimental setup is limited by the system cost and complexity, and the liquid jet method is limited by the availability of sample volume.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Literature shows that the double pulse technique increases the liquid LIBS signal and thereby its sensitivity by using an extra laser pulse to preheat the plasma-induced by the laser in a liquid environment. [20][21][22][23][24][25] In addition, resonance LIBS by choosing a suitable laser wavelength to employ, circulating the sample through a liquid jet, [26][27][28][29] creation of aerosols 30,31 and liquid droplets, 32,33 liquid to solid transformation using different substrates, [34][35][36][37][38][39][40][41] etc., are the other proposed methods for liquid LIBS analysis till date. Among them, adding the components to the experimental setup is limited by the system cost and complexity, and the liquid jet method is limited by the availability of sample volume.…”
Section: Introductionmentioning
confidence: 99%
“…When the primary instrument M(:, i) corresponds one by one with the secondary instrument S(:, j), the univariate regression model is constructed using eqn (1). When the primary instrument M(:, i) corresponds with the secondary instrument from S(:, j − k) to S(:, j + m), the multivariate regression model is constructed using eqn (2), where a linear regression algorithm was used to calculate the equation coef-cients for the univariate regression model and the PLS algorithm was used to calculate the equation coefficients for the multivariate regression model. The transfer model coefficient matrix F is obtained by calculating for the full spectral channel, and the relationship between the primary and secondary instrument spectra can be seen in eqn (3).…”
Section: Transfer Learningmentioning
confidence: 99%
“…Since its discovery in the 1960s, 1 the laser-induced breakdown spectroscopy (LIBS) technique has been applied in the fields of environmental protection, 2–4 military equipment, 5 aerospace, 6,7 medical devices, 8,9 and mining exploration. 10,11 As an atomic emission spectroscopy analysis technique, LIBS uses a high energy density pulsed laser to excite the sample surface, and produces a plasma by ablating the sample, then the emission spectral line signals emitted by the plasma are received by the spectrometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the enrichment behaviours of elements in the complex extraction process would be varied depending on the species and valence state of the elements, resulting in the limited analysis of some elements. 32 Hence, in order to achieve rapid and real-time measurement and obtain strong spectral intensity, double pulse LIBS (DP-LIBS) was developed for liquid sample detection. This DP-LIBS was used in analysis of bulk water by Lazic et al 33 The results showed that the LoD for Cr was determined to be 0.92 μg mL −1 .…”
mentioning
confidence: 99%